Evaluation of ultrafast wave-CAIPI MPRAGE for visual grading and automated measurement of brain tissue volume - Longo, Maria Gabriela; Conklin, J.; Cauley, S. F.; Setsompop, K.; Tian, Q.; Polak, Daniel; Polackal, M.; Splitthoff, D.; Liu, W.; Gonzalez, R. G.; Schaefer, P. W.; Kirsch, J. E.; et al. (American journal of neuroradiology, 2020)
BACKGROUND AND PURPOSE: Volumetric brain MR imaging typically has long acquisition times. We sought to evaluate an ultrafast MPRAGE sequence based on Wave-CAIPI (Wave-MPRAGE) compared with standard MPRAGE for evaluation of regional brain tissue volumes. MATERIALS AND METHODS: We performed scan-rescan experiments in 10 healthy volunteers to evaluate the intraindividual variability of the brain volumes measured using the standard and Wave-MPRAGE sequences. We then evaluated 43 consecutive patients undergoing brain MR imaging. Patients underwent 3T brain MR imaging, including a standard MPRAGE sequence (acceleration factor [R] = 2, acquisition time [TA] = 5.2 minutes) and an ultrafast Wave-MPRAGE sequence (R= 9, TA = 1.15 minutes for the 32-channel coil;R= 6, TA = 1.75 minutes for the 20-channel coil). Automated segmentation of regional brain volume was performed. Two radiologists evaluated regional brain atrophy using semiquantitative visual rating scales. RESULTS: The mean absolute symmetrized percent change in the healthy volunteers participating in the scan-rescan experiments was not statistically different in any brain region for both the standard and Wave-MPRAGE sequences. In the patients undergoing evaluation for neurodegenerative disease, the Dice coefficient of similarity between volumetric measurements obtained from standard and Wave-MPRAGE ranged from 0.86 to 0.95. Similarly, for all regions, the absolute symmetrized percent change for brain volume and cortical thickness showed <6% difference between the 2 sequences. In the semiquantitative visual comparison, the differences between the 2 radiologists' scores were not clinically or statistically significant. CONCLUSIONS: Brain volumes estimated using ultrafast Wave-MPRAGE show low intraindividual variability and are comparable with those estimated using standard MPRAGE in patients undergoing clinical evaluation for suspected neurodegenerative disease.